Population differences in breast cancer severity. (March 2008) - Fejerman, Laura; Ziv, Elad
Breast cancer incidence and mortality vary among different populations. African––American, Hispanic, Asian and Native American women have lower incidence but higher mortality compared with non-Hispanic white women. Explanations for the observed variation include social and economic factors such as education, income level, health insurance coverage, use of mammography, parity, breastfeeding and diet. Breast cancer may be a heterogeneous disease with different subtypes of tumors having different genetic and environmental risk factors. The difference in frequency of particular tumor subtypes between populations may explain some of the differences in incidence and mortality. Known genetic variants explain a small fraction of breast cancer cases, and so far there are no susceptibility genes that explain population differences in incidence and mortality. Studies evaluating the risk for particular tumor subtypes combining genetic and environmental variables and analyzing cases from different populations are needed to understand population differences in the severity of breast cancer.